2019
DOI: 10.1002/sgp2.12011
|View full text |Cite
|
Sign up to set email alerts
|

“She Lied”: Social construction, rape myth prevalence in social media, and sexual assault policy

Abstract: This analysis investigates the presence of rape myths in the policy context, as reflected in social media, and considers how those myths might manifest in policy related to sexual assault in accordance with the social construction theory of target populations. Contested interpretations of Title IX between the Obama and Trump administrations serve as an example of how underlying assumptions about target populations based on rape myths might influence policy design. The rape myth that women routinely lie about r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…This also framed the amendment as an infringement on ethical autonomy, feminism and liberalism. Stabile et al (2019) found similar constructions within their analysis, whereby policymakers were constructed as providing beneficial policy to already advantaged, positively constructed populations (men), and disadvantageous policy for negatively constructed groups (women) (Stabile et al, 2019). Equally, a variety of account holders positioned female MPs who first introduced the bill such as Home Secretary, Priti Patel as unintelligent through derogatory, damaging and discriminatory labels, such as: "foolish, " "Thiki patel, " and "idiot like you, " whilst also being instructed to "resign."…”
Section: Structural Injustice Implications: Policy Requires Reformmentioning
confidence: 99%
See 2 more Smart Citations
“…This also framed the amendment as an infringement on ethical autonomy, feminism and liberalism. Stabile et al (2019) found similar constructions within their analysis, whereby policymakers were constructed as providing beneficial policy to already advantaged, positively constructed populations (men), and disadvantageous policy for negatively constructed groups (women) (Stabile et al, 2019). Equally, a variety of account holders positioned female MPs who first introduced the bill such as Home Secretary, Priti Patel as unintelligent through derogatory, damaging and discriminatory labels, such as: "foolish, " "Thiki patel, " and "idiot like you, " whilst also being instructed to "resign."…”
Section: Structural Injustice Implications: Policy Requires Reformmentioning
confidence: 99%
“…Opposingly, masochism involves sexual gratification experienced while being subjected to physical pain or humiliation by another individual (i.e., powerlessness) ( Lines, 2015 ). Both concepts, allow individuals to express sexual agency, however, such terms are arguably socially constructed ( Stabile et al, 2019 ), and their perceived meaning is likely to alter between contexts and individuals ( Burch and Salmon, 2019 ). Such meanings are therefore important in our understanding of gendered power relations and unequal sexual spaces including within intimate relationships, politics, pornography and the criminal justice system ( Smith and Skinner, 2017 ; Stabile et al, 2019 ; Eaton and McGlynn, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The themes of hashtags represented in the word cloud point to the aspirations of the organizations at hand, which range from education and norm changing, such as expressed in #ItsOnUs and #ChangeTheCulture, to specifically policy‐ relevant themes, including #DearBetsy, #TitleIX, and #INeedIX. In the former category, #ShatteringtheSilence is a tagline for PAVE , while in the latter, both policy actor and policy mechanism are referenced: US Secretary of Education Betsy DeVos, who is persona non grata in anti‐GBV circles due to her support for revisions to the interpretation of Title IX, which are generally seen by activists as a significant setback for survivors (Stabile et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, the online nature of these messages means that many become, over time, watered-down versions of the original sentiments (Gavey, 2012; Windels et al, 2020). Similarly, although Twitter has catapulted several prominent social campaigns (e.g., #MeToo), it is also routinely used to objectify women, perpetuate anti-feminist messages, and has played a key role in the targeted abuse against feminists (Li et al, 2020; Lutzky & Lawson, 2019; Rodriguez & Hernandez, 2018; Stabile et al, 2019). A similar case can be made for the online forum Reddit.…”
Section: Consequences For Societymentioning
confidence: 99%